DIDACTICS ASPECTS OF PREPARATION OF FUTURE DRUGGISTS ARE IN REALITIES OF FORMING OF MODERN HIGHER MEDICAL EDUCATION IN UKRAINE - Рева, Тетяна Дмитрівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
In the article informative sources are generalized and certain problem tasks to development of the domestic system of health protection in modern realities of forming of modern higher medical education in Ukraine. By an author didactics bases of study of course of analytical chemistry future pharmacists as bases of acquisition are outlined reasonable by them professional competences in the educational process of modern higher medical initial establishment